Potential of Using WVO for a Restaurant EV Charging Station - Albatayneh Aiman (Environmental and Climate Technologies, 2022)
This research comprised an evaluation study for a charging station based on waste vegetable oil or biodiesel fuel. The biodiesel was produced from waste vegetable oil (WVO) and will be used (or the WVO) to charge electric cars for restaurant’s customers in their car park. The main concept behind the charging station is to be part of a restaurant that serves its customers and then uses its WVO or biodiesel to fuel a diesel engine that generates electricity to charge their electric vehicles (EV). The economic and environmental impacts of the direct use of WVO-EV charging station are promising because the costs associated with purchasing WVO are lower than those of purchasing crude oil or gas. There are several options and scenarios when selecting the perfect sized generator; using charging up to a maximum rated power of 6.6 kW is more feasible despite its higher initial cost as the simple payback period will be less than 3 years and the internal rate of return of the project is 44 %. The total saving at the end of the project for a generator with maximum rated power of 10 kW (option B) is $ 58 000. Conversely, for a generator with maximum rated power of 6.6 kW (option A) the project will cover its initial cost in around 4 years and the internal rate of return is 26 %. The total saving at the end of the project is $ 52 000. Furthermore, lower amount of greenhouse gases is produced from the burning of WVO directly. The final results showed that WVO is more feasible as it is available for free and could be burnt directly in the diesel engine. In economic terms, the project is feasible for both WVO and biodiesel as it has a high net present value and short payback period. A WVO-EV charging station can also improve the national economy by preparing it for the electric car era and, if applied to a large number of restaurants, will save a significant amount of electricity and reduce the expected strain on the electricity grid caused by the increasing number of electric cars.